A Newly Identified Flower-Specific Splice Variant of AUXIN RESPONSE FACTOR8 Regulates Stamen Elongation and Endothecium Lignification in Arabidopsis. Issue 3 (7th March 2018) - Ghelli, Roberta; Brunetti, Patrizia; Napoli, Nadia; De Paolis, Angelo; Cecchetti, Valentina; Tsuge, Tomohiko; Serino, Giovanna; Matsui, Minami; Mele, Giovanni; Rinaldi, Gianmarco; Palumbo, Gianna Aurora; Barozzi, Fabrizio; et al.
Abstract : ARF8.4, an exitron (exonic intron)-retaining splice variant of AUXIN RESPONSE FACTOR8, regulates stamen elongation and endothecium lignification via its temporal and tissue-specific expression. Abstract: In addition to the full-length transcript ARF8.1, a splice variant ( ARF8.2 ) of the auxin response factor gene ARF8 has been reported. Here, we identified an intron-retaining variant of ARF8.2, ARF8.4, whose translated product is imported into the nucleus and has tissue-specific localization in Arabidopsis thaliana . By inducibly expressing each variant in arf8-7 flowers, we show that ARF8.4 fully complements the short-stamen phenotype of the mutant and restores the expression of AUX/IAA19, encoding a key regulator of stamen elongation. By contrast, the expression of ARF8.2 and ARF8.1 had minor or no effects on arf8-7 stamen elongation and AUX/IAA19 expression. Coexpression of ARF8.2 and ARF8.4 in both the wild type and arf8-7 caused premature anther dehiscence: We show that ARF8.2 is responsible for increased expression of the jasmonic acid biosynthetic gene DAD1 and that ARF8.4 is responsible for premature endothecium lignification due to precocious expression of transcription factor gene MYB26 . Finally, we show that ARF8.4 binds to specific auxin-related sequences in both the AUX/IAA19 and MYB26 promoters and activates their transcription more efficiently than ARF8.2. Our data suggest that ARF8.4 is a tissue-specific functional splice variant that controls filament elongation and endothecium lignification by directly regulating key genes involved in these processes.